Characterization of the antinociceptive and sedative effect of amitraz in horses - Queiroz-Neto, A. [UNESP]; Zamur, G. [UNESP]; Gonçalves, S. C. [UNESP]; Carregaro, A. B. [UNESP]; Mataqueiro, M. I. [UNESP]; Harkins, J. D.; Tobin, T. (Wiley, 1998)
Amitraz, an acaricide used to control ectoparasites in animals has a complex pharmacological activity, including α2-adrenergic agonist action. The purpose of this research was to investigate the possible antinociceptive and/or sedative effect of amitraz in horses. The sedative effect of the intravenous (i.v.) injection of dimethylformamide (DMF, 5 mL, control) or amitraz (0.05, 0.10, 0.15 mg/kg), was investigated on the head ptosis test. The participation of α2-adrenergic receptors in the sedative effect provoked by amitraz was studied by dosing yohimbine (0.12 mg/kg, i.v.). To measure the antinociception, xylazine hydrochloride (1 mg/kg, i.v., positive control) and the same doses of amitraz and DMF were used. A focused radiant light/heat directed onto the fetlock and withers of a horse were used as a noxious stimulus to measure the hoof withdrawal reflex latency (HWRL) and the skin twitch reflex latency (STRL). The three doses of amitraz used (0.05, 0.10 and 0.15 mg/kg) provoked a dose-dependent relaxation of the cervical muscles. The experiments with amitraz and xylazine on the HWRL showed that after i.v. administration of all doses of amitraz there was a significant increase of HWRL up to 150 min after the injections. Additionally, there was a significant difference between control (DMF) and positive control (xylazine) values up to 30 min after drug injection. On the other hand, the experiments on the STRL show that after administration of amitraz at the dose of 0.15 mg/kg, a significant increase in STRL was observed when compared with the control group. This effect lasted up to 120 min after injection. However, no significant antinociceptive effect was observed with the 0.05 and 0.10 mg/kg doses of amitraz or at the 1.0 mg/kg dose of xylazine.
Keywords: acaricide; alpha 2 adrenergic receptor; alpha 2 adrenergic receptor stimulating agent; amitraz; n,n dimethylformamide; xylazine; yohimbine; antinociception; controlled study; dose response; ectoparasite; female; horse; human experiment; intravenous drug administration; latent period; muscle relaxation; neck muscle; nociceptive stimulation; nonhuman; normal human; priority journal; ptosis; sedation; skin; withdrawal reflex; Adrenergic alpha-Agonists; Animals; Dimethylformamide; Dose-Response Relationship, Drug; Female; Horses; Hypnotics and Sedatives; Injections, Intramuscular; Pain Threshold; Receptors, Adrenergic, alpha-2; Toluidines; Xylazine; Animalia; Equidae; Equus caballus